An Assessment of the Contribution of Food Security Projects on Poverty Alleviation in the Communities of Limpopo Province, South Africa - T. J. , Nesengani; M. J. , Mudau; V. O, Netshandama (Current Perspectives in Agriculture and Food Science Vol. 8, 2024)
The study assessed the audit components such as economic components, political components, health and education components, environmental components, and social components, which were used to affirm the economic and material characteristics of the communities. Despite South Africa’s economic growth having been accelerated considerably in the country, poverty levels have not decreased as one would have experienced. Global economic challenges have made it increasingly difficult for governments to meet the food security challenge. Agricultural development through the establishment of food security projects was seen as a panacea for reducing poverty and food insecurity by the government of South Africa. Food Security Projects initiated by the government of South Africa in order to help alleviate poverty within Limpopo Province have proved unsustainable and difficult to provide for what they were mandated to provide to the satisfaction of the government, which is to create jobs and alleviate poverty. The purpose of this study was to assess the contribution of food security projects to poverty alleviation in the communities. The study was conducted in the five districts of Limpopo Province, namely, Mopani, Vhembe, Capricorn, Sekhukhune and Waterberg. In this study, quantitative data was collected through questionnaires which were administered to 50 chairpersons of the food security projects and 5 extension officers who were responsible for overseeing the food security projects in the district. The results affirmed that food security projects were still contributing to poverty alleviation for the beneficiaries although COVID-19 delayed the progress for their growth.